Prognostic Impact of miR-224 and RAS Mutations in Medullary Thyroid Carcinoma - Elisabetta Cavedon; Susi Barollo; Loris Bertazza; Gianmaria Pennelli; Francesca Galuppini; Sara Watutantrige-Fernando; Simona Censi; Maurizio Iacobone; Clara Benna; Federica Vianello; Stefania Zovato; Davide Nacamulli; et al. (International Journal of Endocrinology)
Little is known about the function of microRNA-224 (miR-224) in medullary thyroid cancer (MTC). This study investigated the role of miR-224 expression in MTC and correlated it with mutation status in sporadic MTCs. A consecutive series of 134 MTCs were considered. Patients had a sporadic form in 80% of cases (107/134). In this group, REarranged during transfection (RET) and rat sarcoma (RAS) mutation status were assessed by direct sequencing in the tumor tissues. Quantitative real-time polymerase chain reaction was used to quantify mature hsa-miR-224 in tumor tissue. RAS (10/107 cases, 9%) and RET (39/107 cases, 36%) mutations were mutually exclusive in sporadic cases. miR-224 expression was significantly downregulated in patients with the following: high calcitonin levels at diagnosis (p=0.03, r=−0.3); advanced stage (p=0.001); persistent disease (p=0.001); progressive disease (p=0.002); and disease-related death (p=0.0001). We found a significant positive correlation between miR-224 expression and somatic RAS mutations (p=0.007). Patients whose MTCs had a low miR-224 expression tended to have a shorter overall survival (log-rank test p=0.005). On multivariate analysis, miR-224 represented an independent prognostic marker. Our data indicate that miR-224 is upregulated in RAS-mutated MTCs and in patients with a better prognosis and could represent an independent prognostic marker in MTC patients.